Bridging the divide: unveiling treatment gap and barriers to mental health care for medical students in Pakistan: a cross-sectional study - Jaffar, Maria; Jamana, Zahra; Jaffar, Juwayria; Hashmi, Shameen; Anber, Shafq; Fatima, Sumia; Hashmi, Faria (International Journal Of Community Medicine And Public Health, 2025)
Background: Depression is a common yet often underrecognized and treatable disorder among medical students. In Pakistani cohort there is limited research on barriers to accessing mental health care. This study aims to quantify the treatment gap in mental health conditions among Pakistani medical students, identify potential barriers to initiating mental health treatment, and explore demographic predictors influencing the reporting of these barriers. Methods: A cross-sectional study was conducted between March and July 2025 involving 144 medical students. Data collection utilized the barriers to access to care evaluation (BACE v3) and the Rosenberg self-esteem scale (RSES) questionnaires. Statistical analyses were performed using SPSS version 28 to ensure rigorous examination of the data. Results: The study examined the demographics, self-esteem levels, and barriers to seeking professional mental health care among 144 participants. The findings indicate that the majority 70.8% exhibited medium to high self-esteem, whereas approximately 29.2% reported low self-esteem. The most prominent barriers identified were attitudinal, 95.8% participants endorsing the preference to "solve the problem on my own," and stigma-related, 79.9% expressing concern about “what my family might think. Discussion: Thematic analysis further revealed key barriers, including stigmatizing beliefs, difficulty in disclosing personal issues, a reliance on self-management, and challenges in accessing professional help. Conclusion: Medical students face significant mental health challenges, often hindered by stigma and attitudinal barriers. Improving awareness, reducing stigma, and enhancing access to mental health services in universities are essential. Early intervention and supportive environments can help safeguard their mental well-being and academic success.